Penyerapan Air Dan Kelarutan Bahan Semen Ionomer Kaca Sebagai Penutup Pit Dan Fisur Gigi - Emma Krisyudhanti (JURNAL INFO KESEHATAN, 2018)
BACKGROUND: Pit and fissure sealants are materials that are often used for preventive maintenance, especially on occlusal surfaces of teeth that are susceptible to caries. All restoration materials that come into contact with water will experience 2 mechanisms, namely the absorption of water, which causes matrix swelling and increased mass and water solubility, namely the release of components from unreacted monomers and causing reduced mass. OBJECTIVE: Measure the value of water absorption and solubility of glass ionomer cement as a cover of the pit and fissure of the tooth. METHODS: 18 specimens of glass ionomer cement sealant material manipulated according to the manufacturer's instructions consisted of six specimens measuring 15 mm in diameter and 1 mm in thickness made for each immersion time. The specimen was put into a desiccator at 37°C for 22 hours and then put into another desiccator with a temperature of 23°C for 2 hours. The specimen was weighed with a precision scale of 0.1 mg. Measurements are carried out repeatedly until a constant mass is obtained (M1). Next, the specimen was put into 40 ml of aquabides and stored in a desiccator at 37°C for 1 day, 2 days and 7 days. At the end of each immersion time, the specimen was removed from aquabides, dried with suction paper and vibrated in the air for 15 seconds. Specimens are weighed to get M2. The specimens were reconditioned to the desiccator at 37°C for 22 hours and then put into another desiccator with a temperature of 23°C for 2 hours and this procedure was repeated one day later, then the mass was weighed repeatedly until a constant mass was obtained (M3). RESEARCH RESULTS: The Kruskal-Wallis statistical test shows that there is no significant difference in the average water absorption value and solubility of materials for immersion for 1 day, 2 days and 7 days. CONCLUSIONS AND RECOMMENDATIONS: The absorption rate of glass ionomer cement as a cover of dental pit & fissure decreased until the second day and increased until the seventh day, with an average absorption of water for 1 day immersion of 42.68mg/mm³, 2 days 40, 53mg/mm³ and 7 days 42.99mg/mm³. Solubility value in water of glass ionomer cement as a cover of dental pit & fissure decreased until the second day then increased until the seventh day, with an average solubility of material for immersion for 1 day at 41.46mg/mm³, 2 days 39.39mg/mm³ and 7 days 41,91mg/mm³. It was said that there was no significant difference in the value of water absorption and solubility of materials during the immersion period of 1, 2 and 7 days. It is recommended that in the application of glass ionomer cement as a cover of dental pits and fissures, please note in the provision of varnish or protector to reduce the occurrence of water absorption and solubility of the material. In addition, the pit and fissure of the tooth that has been covered should be controlled 3 months later to find out if the cover is still intact or has been damaged or loose. It is also recommended that there is further research to determine the value of water absorption and solubility of ingredients if soaked in artificial saliva for more than 7 days.